Development of Environmental Health Indicators for the Child Population: Report on a Brazilian Experience - Flavia Franchini de Moraes; Volney de Magalhaes Camara; Carmen Ildes R. Froes Asmus (Ubiquity Press, 2017)
Background: This report presents the Brazilian experience on the elaboration of a matrix of children's environmental health indicators to the Brazilian Health Surveillance System. This experience was part of a project with the financial support of the Ministry of Health of Brazil to develop appropriate indicators for identification, measuring, and monitoring of the environmental risk factors to the children's health. Methods: The methodology adopted for the development of the matrix of indicators of children's environmental health to Brazil comprised 3 steps. In the first step, the main causes of morbidity and mortality in the Brazilian population, aged 0-14 years, were identified, according to the data available from the Ministry of Health. The second step consisted of the identification of the Brazilian public-access information systems, with available official data regarding environmental, health, and socioeconomic conditions. In the third step, a preliminary matrix was elaborated. Correlation analyses were done to determine the indicators that would constitute the final matrix. Findings: The selected indicators allowed the identification and surveillance of cancer, injuries, adverse birth outcomes, diarrheic and respiratory diseases, associated with environmental risk factors, in the Brazilian child population. The existing Brazilian official information systems provided data with the necessary quality for the construction of children's environmental health indicators. Nevertheless, some official systems on health information presented limitations related to the data availability over the course of time and timeliness of data capture. Concerning the environmental information, the major limitation was accessibility. Conclusions: A matrix of indicators of children's environmental health to Brazil can come to contribute to the implementation of a surveillance system of children's exposure to environmental contaminants in Brazil.